Relações empíricas para estimativa da resistência ao arrancamento de ancoragens - D'Hyppolito, Lays Cristina Barcelos de Souza (2017)
This work presents a database created after an extensive research in the national literature, from the reporting on tests with information on site, soil type, anchorage type, test methods and pullout resistance methods of determination. The database consisted of 445 tests, of which 24 were developed in laboratory and the others in situ. The majority of the tests were carried out between Rio de janeiro and São Paulo. In addition, only Minas Gerais and Brasília presented representative numbers of tests. The analysis were done by region, soil type, executive method, direct and indirect resistance parameters. Despite the inherent dispersions associated to the wide database, the study resulted in a proposal of a new correlations between the pullout resistance and the NSPT index based on the Brazilian test results, which can be adopted for project purposes.